Specialized Software for Teaching Differential Equations (SCIÉNDO INGENIUM, 2023)
In the third semester Multivariable Calculus course, Systems and Computer Engineering major at the Universidad Nacional Alcides Carrión; in the teaching of differential equations, a specialized software (Matlab R2019b) was used with the purpose of strengthening learning; A survey was applied to 25 students both at the beginning and at the end of the class, using a questionnaire with 10 questions, sized on the reliability of the software, algorithms for the development of integrals, visualization, simulation, mathematical concepts and understanding of physical phenomena, mathematical modeling techniques, mastery of information technologies, and manipulation of real-world objects. The main result achieved was the knowledge of the solution of ordinary differential equations, where before the development of the class, 80% of students believed they did not know the subject; however, using the specialized software, it decreased to 72%. Likewise, in the scale of knowing completely, it went from 16% to 28%. After applying the Kruskal-Wallis statistical test with a reliability of 95%, it was concluded that there was an increase in learning, given that the p-value was 0.041, less than 0.05.
Keywords: differential equations; multivariate calculus; learning; specialized software; mathematics teaching